Staphylococcus aureus plasmids without mobilization genes are mobilized by a novel conjugative plasmid from community isolates - O'Brien, Frances; Ramsay, J.; Monecke, S.; Coombs, Geoffrey; Robinson, O.; Htet, Z.; Alshaikh, F.; Grubb, W. (Oxford University Press, 2015)
Objectives: To describe a family of conjugative plasmids isolated from colonizing community Staphylococcus aureus and determine their ability to mobilize unrelated antimicrobial resistance/virulence plasmids, not encoding mobilization functions. Methods: Plasmid pWBG749 was labelled with Tn551 (pWBG749e) to enable laboratory manipulation. Plasmid pWBG749e was conjugated into S. aureus of seven different lineages that harboured unrelated plasmids and mobilization experiments were performed. Plasmids were screened by EcoRI restriction and hybridization with probes prepared from unique pWBG749 conjugation genes. Results: Conjugative plasmids pWBG745, pWBG748 and pWBG749 belong to the same conjugative-plasmid family as the vancomycin resistance plasmid pBRZ01. Plasmid pWBG749e mobilized five unrelated plasmids. Mobilized plasmid pWBG744 is a pIB485-family plasmid that was also found in international S. aureus. Conclusions: Plasmid pWBG749e can mobilize unrelated S. aureus plasmids whose means of dissemination have not previously been understood.